2014
DOI: 10.1108/ijppm-08-2013-0143
|View full text |Cite
|
Sign up to set email alerts
|

Understanding third sector performance measurement system design: a literature review

Abstract: Purpose – The purpose of this paper is to examine the literature on third sector performance measurement system design. Design/methodology/approach – A systematic literature review was undertaken. The abstracts of 917 articles identified from a database search were examined and, of these, 110 papers were put forward for full paper review. Totally, 55 papers were subsequently selected for the literature synthesis. Findings – The findings examine the important questions of why and how the performance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0
12

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(71 citation statements)
references
References 58 publications
2
57
0
12
Order By: Relevance
“…This paper therefore will explore the term 'Integrated Performance Management' (IPM), focussing on the integration of internal and external reporting, and the underpinning integrated collection and use of data and information through a range of sources. This terminology is in line with Moxham (2014) as discussed above.…”
Section: Integrated Performance Managementsupporting
confidence: 49%
See 1 more Smart Citation
“…This paper therefore will explore the term 'Integrated Performance Management' (IPM), focussing on the integration of internal and external reporting, and the underpinning integrated collection and use of data and information through a range of sources. This terminology is in line with Moxham (2014) as discussed above.…”
Section: Integrated Performance Managementsupporting
confidence: 49%
“…Organisations such as New Philanthropy Capital are developing performance indicators and benchmarks for the sector (Connolly & Hyndman 2013). Moxham (2014), through a systematic review of current literature, finds that TSOs are driven to measure performance for reasons of accountability (to multiple stakeholders), legitimacy and efficiency (allocation of resources and effectiveness of activities). Moxham's review found that the most prevalent methods of measurement are reputational (based on surveys of staff, beneficiaries, partners) and multi-dimensional (employing several different methods for measuring).…”
Section: Introductionmentioning
confidence: 99%
“…The authors also state that the adoption of a model is not just a strategic tool for these organizations, but a condition of existence and survival. Because their function is of public interest, it is important that NPOs cultivate transparency regarding their project portfolio (Marcovitch 1997), as well as results achieved and resources allocated (Kaplan 2001;Marcovitch 1997), which further enhance the effective and transparent implementation of their resources (Moxham 2014;Oliveira, Ross & Altimeyer 2005). In this sense, the following discussion considers PPM and dimensions related to the operational, tactical, and strategic levels of organizations.…”
Section: Management Systems In Nposmentioning
confidence: 99%
“…Management in the nonprofit sector is a strategic issue related to efficient operation and effective performance in accomplishing missions and goals (Moxham 2014;Machado, Francisconi & Chaerki 2007;Albuquerque 2006). In this sense, Falconer (1999) identified four dimensions needed to develop management that can be generalized to the sector as a whole: stakeholder accountability, sustainability, service quality, and articulation capacity.…”
Section: Management Systems In Nposmentioning
confidence: 99%
See 1 more Smart Citation